Harmonically mode-locked femtosecond fiber laser using non-uniform, WS2-particle deposited side-polished fiber. (22nd February 2016) - Lee, Junsu; Park, June; Koo, Joonhoi; Jhon, Young Min; Lee, Ju Han
Abstract: We investigated the feasibility of using a WS2 -deposited side-polished fiber as a harmonic mode-locker to produce a femtosecond fiber laser with a frequency of 1.51 GHz. Our work focuses on using a side-polished fiber platform with non-uniform WS2 particles prepared through liquid phase exfoliation method without centrifugation. Femtosecond optical pulses were generated from an all-fiberized erbium-doped fiber-based ring cavity by increasing the pump power to achieve a tunable pulse repetition rate from 14.57 MHz to 1.51 GHz (104th harmonic). The characteristics of the output pulse were systematically investigated to analyze the pulse repetition rate, harmonic order, average output power, pulse energy, and pulse width as a function of the pump power. The output performance of the laser was compared to that of a laser based on a microfiber-based WS2 film SA described in (Yan et al 2015 Opt. Mater. Express 5 479–89 ). This experimental demonstration reaffirms that a side-polished fiber is an effective platform to implement an ultrafast harmonic mode-locker, and non-uniform WS2 particles prepared via simple liquid phase exfoliation method without centrifugation provide a suitable saturable absorption response at 1.55 μ m.